1996
DOI: 10.1029/96ja00003
|View full text |Cite
|
Sign up to set email alerts
|

First detection of charged dust particles in the Earth's mesosphere

Abstract: Some theories for the observed anomalous radar backscatter during the summer (polar mesospheric summer echoes, or PMSE) and electron bite outs measured by rockets require the presence of charged dust. To investigate this, two dust probes have been launched in 1994 from Andøya Rocket Range and we here report the results from the dust and an electron probe on the two payloads. The dust probes were designed to block out the electron and ion components at the mesopause but to detect primary currents due to impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
401
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 447 publications
(416 citation statements)
references
References 23 publications
14
401
0
Order By: Relevance
“…The currents from G1, G2 and the gold-plated DC are all measured. The EDD probe is similar to the original DUSTY probe (Havnes et al, 1996) but the shape of the grids has been altered to change the production of secondary charges from the impacting dust particles. Also, the G1 wire thickness was reduced from 0.8 mm on DUSTY to 0.25 mm, resulting in a reduction of the ratio of the dust probe opening which is covered, from σ 1 =0.23 to 0.08.…”
Section: The Dust Experiments and The Launch Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The currents from G1, G2 and the gold-plated DC are all measured. The EDD probe is similar to the original DUSTY probe (Havnes et al, 1996) but the shape of the grids has been altered to change the production of secondary charges from the impacting dust particles. Also, the G1 wire thickness was reduced from 0.8 mm on DUSTY to 0.25 mm, resulting in a reduction of the ratio of the dust probe opening which is covered, from σ 1 =0.23 to 0.08.…”
Section: The Dust Experiments and The Launch Conditionsmentioning
confidence: 99%
“…It is now becoming increasingly clear that secondary charging effects, due to impacting dust particles on rocket payloads and their probes, can affect some measurements (Zadorozhny et al, 1993;Havnes et al, 1996;Vostrikov et al, 1997;Gumbel and Witt, 1998) and probably sometimes totally dominate them (Barjatya and Swenson, 2006;Havnes and Naesheim, 2007). In the last paper, it was demonstrated that secondary charging by dust particles impacting on surfaces at a high impact angle θ i (= angle with the normal to the surface), which fragmented and carried away negative charge, could give the appearance of incoming positive charges.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations